The pattern and processes of genome change in endosymbionts old and new : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Evolutionary Biology, Institute of Molecular BioSciences, Massey University, New Zealand - Schönfeld, Barbara Inge Karoline (Massey University, 2012)
Bacterial endosymbionts are an important part of eukaryote evolution as they allow their hosts to exploit bacterial abilities. Plastids, the organelles that enable plant and eukaryotic algae tophotosynthesise are ancient cyanobacterial endosymbionts. Since the initial symbiosis ~1.5 billion years ago the majority of their genes has been lost or transferred to their host’s nucleus. This process has carried on independently in the different lineages following the diversification of the lineage. I have compiled a comprehensive data set of fully sequenced plastid genomes to systematically study the frequency of gene transfers from the plastid to the nucleus across the different lineages.Following the reconstruction of the Plantae phylogenetic tree from plastid encoded proteins, gene loss events were reconstructed along its branches. My calculations show that gene losses have occurred at a relative high frequency and in a lineage specific way. This challenges the original idea that gene transfers from the organelle to the nucleus are rare and chance driven events. Bacteria and eukaryotes continue to form endosymbioses and the study of these relationships produces valuable insights into the early stages of organelle evolution, bacterial metabolic pathways and metabolic regulation. They also allow us a glimpse into the ancient history of eukaryote evolution. For this reason, diatoms that have acquired cyanobacterial endosymbionts with the capability to fix molecular nitrogen were chosen to explore the potential and limitations of high-throughput sequencing technologies for investigating this type of relationship when DNA sequences are obtained from environmental samples and in the presence of bacterial contaminants. The results of this work confirmed the suitability of this relatively new technology to sequence mixed samples but also highlighted i) difficulties in sample preparation which can bias the composition of metagenomic samples obtained, and also ii) the varying suitability of different types of samples used in high-throughput sequencing.
Keywords: Eukaryotic cells; Genetics; Evolution; Endosymbiosis; Endosymbionts; Genome change